1992
DOI: 10.1038/357698a0
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations in a yeast protein resembling HIV Tat-binding protein relieve requirement for an acidic activation domain in GAL4

Abstract: The acidic transcriptional activation motif functions in all eukaryotes, which suggests that it makes contact with some universal component of the transcriptional apparatus. Transcriptional activation by the yeast regulatory protein GAL4 requires an acidic region at its carboxyl terminus. Here we implement a selection scheme to determine whether GAL4 can still function when this C-terminal domain has been deleted. It can, when accompanied by a mutation in the SUG1 gene which is an essential gene in yeast. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
159
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 18 publications
4
159
0
4
Order By: Relevance
“…The results of genetic and transfection experiments have also indicated that some of these ATPases participate in transcriptional regulation. It has been suggested that yeast SUG1 acts as a mediator for a transcriptional activator in vivo (Swaffield et al 1992), and Trip1 (human SUG1) and mouse SUG1 were demonstrated to interact with various hormone receptors (Lee et al 1995;vom Baur et al 1996). Recently, mouse SUG1 was demonstrated to have a DNA helicase activity .…”
Section: Are Proteasomal Atpases Candidates For Transcriptional Regulmentioning
confidence: 99%
“…The results of genetic and transfection experiments have also indicated that some of these ATPases participate in transcriptional regulation. It has been suggested that yeast SUG1 acts as a mediator for a transcriptional activator in vivo (Swaffield et al 1992), and Trip1 (human SUG1) and mouse SUG1 were demonstrated to interact with various hormone receptors (Lee et al 1995;vom Baur et al 1996). Recently, mouse SUG1 was demonstrated to have a DNA helicase activity .…”
Section: Are Proteasomal Atpases Candidates For Transcriptional Regulmentioning
confidence: 99%
“…This complex, termed APIS (1), is argued to act independent of the 26S proteasome as a transcriptional chaperone that facilitates protein-protein interactions necessary for transcriptional activation. Support for APIS comes from genetic and biochemical evidence tying 19S base components to transcriptional activation domains (1,2), and from results of chromatin immunoprecipitation (ChIP) experiments showing that 19S base proteins are recruited to activated genes separately from 20S core components (1, 3, 4). These observations, however, are countered by reports that the proteolytic activity of the proteasome is important for transcriptional activation in yeast (5,6) and for repression of cryptic transcription in mammalian cells (7), and by the finding that 20S proteins also associate with active chromatin by ChIP, albeit with different temporal and spatial distributions than 19S proteins (1,8).…”
mentioning
confidence: 99%
“…It is conceivable that the DNAbinding proteins exert their effects either through intermediary factors termed coactivators (sometimes called mediators or adaptors) or directly on the general transcription factors (4). Candidates for coactivators, which are required for the activator-induced transcription but not for the basal transcription, have been identified in yeast (5)(6)(7)(8)(9) and mammalian cells (10)(11)(12)(13).…”
mentioning
confidence: 99%